Auxin originated from Actinobacteria participates in abiotic stress mitigation and sustainable crop production - Wiem ALLOUN; Hadjer KECIS; Samah CHAOUA; Bertrand CORNU; Hadjer DJELID; Maroua GARES; Noreddine KACEM CHAOUCHE (Notulae Scientia Biologicae, 2023)
Plants activate their defence mechanisms to prevent damage caused by environmental stimuli through signaling pathways controlled by growth regulators. These stresses adversely affect plants' growth, disrupting the genetic control of cellular pathways and altering their metabolism, physiology and morphology. Auxin influences phenotypic plasticity under optimal and unfavourable growth conditions. This review discusses the progress in the research on auxin-mediated stress alleviation in response to abiotic stresses in plants. Then, a brief presentation of studies emphasizing the significance of auxin-producing actinobacteria and how microbial auxin promotes plant development and stress tolerance. Then, the review probes the importance of actinobacteria strains as auxin metabolic engineers and their use as natural auxin suppliers in agriculture. Finally, the review explores future biotechnology possibilities through small-scale, large-scale production and agriculture's gradual banishment of chemical phytosanitary inputs.